2018
DOI: 10.3347/kjp.2018.56.4.385
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis on the Cystic Echinococcosis Cases Occured in Northeastern Punjab Province, Pakistan

Abstract: A retrospective study was performed to report the case occurrence of cystic echinococcosis (CE) in three hospitals of north-eastern region in Punjab Province, Pakistan. We reviewed retrospectively the clinical records of patients in 4 hospitals which were diagnosed with CE during 2012–2017. A total of 198 cases, 82 (41.4%) male and 116 (58.6%) females were detected as CE. The most Highest incidence was revealed in.... 21–30 years-old group (24.2%) followed by 41–50 (22.7%), 31–40 (16.2%), 11–20 (13.6%), 51–60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…CE is an endemic disease in Pakistan and causes serious economic losses in terms of human healthcare and livestock agriculture costs. In addition, there is lack of knowledge about CE in Pakistan that affects its transmission dynamics [34][35][36]. Agriculture is the backbone of the Pakistan and a large number of families are affiliated with this sector, including animal rearing and dairy farming for milk products.…”
Section: Discussionmentioning
confidence: 99%
“…CE is an endemic disease in Pakistan and causes serious economic losses in terms of human healthcare and livestock agriculture costs. In addition, there is lack of knowledge about CE in Pakistan that affects its transmission dynamics [34][35][36]. Agriculture is the backbone of the Pakistan and a large number of families are affiliated with this sector, including animal rearing and dairy farming for milk products.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of hospital records from five major metropolitan cities of Pakistan reported 188 surgically confirmed cases of CE corresponding to an annual frequency of 18.8 cases/year [17]. Another retrospective study in Northeastern Punjab Province reported a total of 198 cases of CE during a 6-year period (2012-2017) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 14.7% of infected stray dogs are in close proximity to humans as well as their livestock, hence maintaining the CE cycle. 24,25 Increasing awareness among the general population is therefore of paramount significance to curb this disease, especially. as a previous study has shown that only 4.1% of dog owners and butchers in Pakistan had even heard about the disease.…”
Section: Discussionmentioning
confidence: 99%